Penentuan Desa Terbaik dengan Menerapkan Kombinasi Metode ROC dan SMART - Margolang, R. Siddik; Fakhriza, Muhammad (Journal of Computer System and Informatics (JoSYC), 2024)
The problem that is used as a reference in this research is the assessment process which still uses the old method, namely by opening pages of documents, so this method takes a lot of time and energy in the assessment process and allows tolerance of values ​​that are similar, making it very difficult to determine the best village. The process of selecting the best village is a very important stage in building a competent and innovative village. The system built using the ROC and SMART methods aims to help data collectors reduce time in data collection and be effective in determining the best villages according to the criteria used. The criteria used are Village Cleanliness (K1), Education (K2), Economy (K3), Security and Order (K4), Role of the PKK (K5), Village Governance (K6) with 7 alternative data samples. Data for this research was collected through interviews and observations at the Rahuning District Office and processed using the ROC and SMART methods for weighting and evaluating decisions. The results of calculations using the ROC and SMART methods found that among the best villages, Gunung Melayu Village was a worthy candidate to become the best village candidate by obtaining a total score of 0.738889.